Kinerja Penyuluh Pertanian Terhadap Kelompok Tani Mega Mendiri Di Desa Kolongan Kecamatan Kalawat - Marco M. Sambeka; Olfie L.S. Benu; Celcius Talumingan; Yolanda P.I. Rori (Universitas Sam Ratulangi, 2015)
ABSTRACT Agricultural extension is one of the school education system that taught farmers effectively and efficiently. Through agricultural extension, farming cummunities equipped with science, skills, the introduction of a new package of technology and innovation in agriculture, cultivation of values or principles agribusiness, creation of human resources with the basic concepts of philosophy diligent, cooperative, innovative, creative, and so on.Â The method of data collectionwas doneby usingprimary dataandsecondary data. Primary dataobtainedfrom interviewswithrespondentsusingaquestionnaire thathas been prepared, while thesecondary dataobtainedfrom theoffice ofthe villageassociated withthisresearch.Â Â The results of this study demonstrate the performance of agricultural extension to farmers groups Mega Mandiri in the kolongan village district kalawat based on 9 (nine) indicators that have become benchmarks assessing the success of agricultural extension is good. Key Words : Performance, Agricultural extension, Farmers